2019
DOI: 10.20944/preprints201909.0212.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral Innate Immune Evasion and the Pathogenesis of Emerging RNA Virus Infections

Abstract: Positive-sense single-stranded RNA (+ssRNA) viruses comprise many (re-)emerging human pathogens that pose a public health problem. Our innate immune system and in particular the interferon response form the important first line of defense against these viruses. Given their genetic flexibility, these viruses have therefore developed multiple strategies to evade the innate immune response in order to optimize their replication capacity. Already many molecular mechanisms of innate immune evasion by +ssRNA viruses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 144 publications
1
82
0
Order By: Relevance
“…Other studies have concluded that this therapy does not have a beneficial effect on patients [38,42].…”
Section: Approach For Sars-cov-2-related Disease Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have concluded that this therapy does not have a beneficial effect on patients [38,42].…”
Section: Approach For Sars-cov-2-related Disease Therapymentioning
confidence: 95%
“…DUB is another role of PLpro to help coronavirus evade attack from a host's immune response by antagonizing the IFN response. From these findings, we hypothesized that the decline in function of the two proteins may lead to the direct introduction and sticking of immune troops to continuously infected cells and prevented the replication of the virus and the life cycle [37,38]. In addition to using nonstructural proteins, SARS-CoV could utilize its protein accessories to avoid immune responses.…”
Section: Immuno-evasion Of Coronavirusesmentioning
confidence: 99%
“…When a virus invades the host, PRRs initially recognize the viral nucleic acid, collect the specific signal adapter protein, activate IRF3 and IRF7 before being translocated to the nucleus and promote the synthesis of type I interferons (IFNs). Type I IFNs subsequently activate the downstream JAK‐STAT signal pathway, promote the expression of IFN‐stimulated genes (ISGs) 37,38 …”
Section: Innate Immune Responsementioning
confidence: 99%
“…SARS-CoV has developed multiple strategies to evade the innate immune response in order to optimize its replication capacity. 61 It seems likely that SARS-CoV-2 uses the same strategy. The magnitude of the immune response against SARS-CoV-2 needs to be precisely calibrated to control viral replication without triggering immunopathogenic injury.…”
Section: Immunopathogenesis Of Sars-cov-2 and Implication For Managemmentioning
confidence: 99%